If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 + -3x = 5x + -1 Reorder the terms: 39 + -3x = -1 + 5x Solving 39 + -3x = -1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 39 + -3x + -5x = -1 + 5x + -5x Combine like terms: -3x + -5x = -8x 39 + -8x = -1 + 5x + -5x Combine like terms: 5x + -5x = 0 39 + -8x = -1 + 0 39 + -8x = -1 Add '-39' to each side of the equation. 39 + -39 + -8x = -1 + -39 Combine like terms: 39 + -39 = 0 0 + -8x = -1 + -39 -8x = -1 + -39 Combine like terms: -1 + -39 = -40 -8x = -40 Divide each side by '-8'. x = 5 Simplifying x = 5
| 15z-5z-3z-6z-1=3 | | 2A+3=27 | | 9h-4h+5h+3=13 | | 2(1x+5)-3=-(2x+1)+1 | | 4x-36=2(3x-4)-10 | | 7a+a-7=17 | | 2(5x-5)+7=5x-8 | | 5/11x | | 4x+34=2(4x-4)+6 | | 482/6 | | -4=2(2x+1)+10 | | 4x+33=-7 | | 20=2c+5 | | -9x+3+4x=.5(2x+66) | | 7*1/2401 | | 12+m=7m+6(2-m) | | -5x+47=2(4x-4)+3 | | 6/1*3/22 | | 4(3x-1)-1=-41 | | .5(3/4)^3 | | 8(4k+9)=-29+7k | | 2(9+6f)=25 | | 3x-2+5=22 | | 0=8y+8 | | -6(9z+8)=-23 | | 2s+12=-4 | | -7-5t=-6t | | 6-j=j | | 8=4e+12 | | -4=2s-2 | | 5p+9=8p | | 0=55-(3x-2) |